STRATEGI PELAYANAN PUBLIK DI KELURAHAN BUKIT PINANG KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Vinolis Friandoni H (Jurnal Administrative Reform, 2017)
The purpose of this study is to identify and explain the strategy of public services at the Village Office Bukit Pinang and describe and analyze strategies village government in improving public services in the village of Bukit Pinang Village. The results showed that the Government Sub Bukit Pinang Kota Samarinda in strategies at the public service, there are five basic strategy, the strategy of development of the structure, strategy development or the simplification of procedures, strategic infrastructure development, cultural development strategy/culture, entrepreneurship development strategy.